Hyaluronic acid in vulvar and vaginal administration: evidence from a literature systematic review. (2nd November 2021) - Buzzaccarini, G.; Marin, L.; Noventa, M.; Vitagliano, A.; Riva, A.; Dessole, F.; Capobianco, G.; Bordin, L.; Andrisani, A.; Ambrosini, G.
Abstract: Vulvovaginal pathology impairs the quality of life of both women in menopause and those who are not. Different therapies have been proposed, mainly related to estrogen therapy in postmenopausal women. However, some contraindications limit its use, and different moisturizers or lubricants have been tested. Hyaluronic acid is a promising and widely used vaginal medical treatment with a moisturizing action and appears to provide a solution. For this reason, we performed a systematic review of the literature. We searched for original articles without date restriction until 30 April 2020. We included all clinical trials which administered local hyaluronic acid in the vulva or vagina. Only English studies and those performed in humans were eligible. Seventeen original studies were included in the review (from randomized controlled trials to longitudinal studies). Hyaluronic acid was generally found to be effective in improving vulvovaginal symptoms (dyspareunia, itching, burning, dryness) and signs (bleeding, atrophy, vaginal pH). In conclusion, hyaluronic acid has the properties to be an efficient moisturizer for women suffering from vulvovaginal atrophy who have contraindications for estrogen therapy and for vulvovaginal signs and symptoms affecting sexual well-being. However, a well-designed randomized controlled trial is needed in order to clarify its efficacy and safety profile.